Preliminary notes on the macrolichens of Serra do Cachimbo, northcentral Brazil - Brako, Lois; Dibben, Martyn J.; Amaral, Iêda Leão do (Acta Amazonica, 1985)
This paper reports on the April-May 1983 Projeto Flora expedition to Serra do cachimbo in northcentral Brazil, a phytogeographically poorly known area near the transition between the Amazon forest and the central Brazilian planalto. The objective of this expedition was to collect botanical specimens with special emphasis on lichens. Rock outcrops are common in this area and several soil types combined with varied topography give rise to a diversity of vegetation types including Amazon caatinga, campo rupestre, gallery forest and Amazon forest. A preliminary checklist of 91 macrolichens is provided with a discussion of ecological distribution of lichens in each habitat.